Virtual reality art-making for stroke rehabilitation: Field study and technology probe. Issue 145 (January 2021) - Alex, Marylyn; Wünsche, Burkhard C.; Lottridge, Danielle
Highlights: In a three-week field study of traditional art-making by 14 stroke survivors with disabilities, we found that these artists utilized the physical and temporally unfolding properties of the materials to create beauty without excessive fine motor precision, used a social, situated and reflective process of tool selection, and created work that blended inspirations and accomplishments from their previous and current identity. We contrasted themes derived from the field study and experiential virtual reality interviews using state of the art 3D tools as a technology probe. We found that the affordances of VR as a medium shifted making away from meditative, physicallysupported fine motor activity to free form mid-air gesture. The experience was immersive, physical and out of control and creations were at times abstract, intentional or emergent. Implications for the design of VR art-making identified from two types of research inquiry. The contrast of the social, reflective and unhurried nature for traditional artmaking and the unfolding of traditional materials, with the speed, proximity and finality of 3D paint lead us to recommend social, situated, reflective, physical and meaningmaking considerations for VR art interaction. Abstract: How can we better understand the process of therapeutic art-making for stroke rehabilitation, and what are design opportunities for virtual reality art-making for people with stroke-related impairments? We investigated this question in a two-part study with 14 amateur artists with disabilities resulting from stroke: a three-week field study and a technology probe consisting of experiential virtual reality interviews. We uncovered what participants made, the aesthetics of the materials and the process of making. The field study revealed inspirations around identity, situatedness of choices for tools in the social and physical environment, and a breadth of application techniques (e.g., dripping paint or use of tape) that varied in need for fine motor control. The experiential virtual reality interviews highlighted the need for control, the affordances of the medium, and the challenges in viewing and reflecting on work. Emergent art reflected qualities of the 3D paint and free-form gesture. Virtual reality and traditional art-making contrasted in the speed and finality of application, opportunities for iteration and reflection, and in the need for dexterity. We discuss strengths, weaknesses and implications for design of virtual reality art-making for those with stroke-related impairments.